MARKETING STRATEGY ANALYSIS OF CV. PUTRA SAWIT'S PALM OIL RAMP BUSINESS IN MUSAN VILLAGE, PARINDU DISTRICT, SANGGAU REGENCY, WEST KALIMANTAN - Dian Andhiny; Junaidi (RADJA PUBLIKA, 2026)
Palm oil is a strategic plantation commodity that plays an important role in the national economy. The high production of fresh fruit bunches (FFB) in Parindu District, Sanggau Regency, has encouraged the development of ramp businesses as marketing institutions that connect farmers with palm oil mills. Increasingly tight competition between ramps requires companies to have appropriate marketing strategies to be able to attract and retain farmers as suppliers. This study aims to analyze internal and external factors that influence marketing and formulate appropriate marketing strategies for CV. Putra Sawit in Musan Village, Parindu District, Sanggau Regency. The study was conducted from March to May 2026 using a qualitative descriptive method. Research informants were selected purposively, consisting of company owners, farmers who actively sell FFB to CV. Putra Sawit, and farmers who have switched to other ramps . Data collection was carried out through in-depth interviews, observation, and documentation, while data analysis used data reduction, data presentation, and conclusion drawing. Internal and external factors were analyzed using the IFAS and EFAS Matrices, then alternative strategies were formulated through the SWOT Matrix. The results of the study indicate that CV. Putra Sawit's marketing strategy is influenced by price, service quality, business location, relationships with farmers, transaction transparency, and trust levels. IFAS and EFAS analyses indicate that the company has greater strengths and opportunities than weaknesses and threats, thus being in a condition that supports the implementation of a growth strategy. The recommended strategy is to improve transaction transparency, service quality, communication of price information, and strengthening relationships with farmers to increase supplier loyalty and company competitiveness. The implementation of these strategies is expected to increase the volume of FFB receipts and maintain the sustainability of CV. Putra Sawit's business in facing competition.